Karakteristik Alterasi dan Mineralisasi Hidrotermal Daerah Hulawa, Gorontalo, Indonesia - Umar Zulkarnain Bakkar; Muhammad Kasim; Noviar Akase; Ahmad Iryanto Rompo (Universitas Negeri Gorontalo, 2020)
Gold is one of the precious metals with high economic value, so the exploration process becomes an important stage to find new resources so that gold production remains optimal. The research was aimed at investigating the geological condition and characteristics of hydrothermal alteration and mineralization developed in the research site. The research site was included in the area CoW of PT. Gorontalo Sejahtera Mining exactly lied in Hulawa Village, Gorontalo, Indonesia. This research integrated the fieldwork with laboratory tests and analysis, including petrography, Analytical Spectral Devices, and mineragraphy. Based on data that had been conducted and data analysis results, it can be concluded that the research site consisted of lithology in the form of Oligocene granodiorite and Pliocene rhyodacite and diatreme breccia that rolled as host rock’s mineralization. Normal right-slip fault directing E-W is interpreted as a pre-mineralization structure, while normal left-slip fault directing NNE-SSW is interpreted as syn-mineralization structure or controlling structure during alteration and mineralization process. Alteration developed in research area consisted of the phyllic zone (sericite + quartz ± pyrite ± montmorillonite ± chlorite ± carbonate), argillic zone (illite + kaolinite ± smectite ± montmorilonite), and chloritic zone (chlorite + carbonate + pyrite ± quartz ± illite ± sericite ± montmorillonite). Hydrothermal deposits controlled by geological structure and volcanic mechanism. Mineralization in the research site was found in stockwork quartz veins and hydrothermal breccia, and some were found in dissemination with ores such as pyrite, chalcopyrite, arsenopyrite, galena, sphalerite, bornite, covelite, gold, and electrum. Based on its alteration and mineralization characteristics, the epithermal deposits in the research site was the type of low sulphidation deposite in-depth level in the model of open-vein and breccia.